2006
DOI: 10.1111/j.1600-0609.2006.00644.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of bone marrow involvement in patients with diffuse large cell lymphoma varies according to the degree of infiltration and presence of discordant marrow involvement

Abstract: Minimal BMI, seen in the majority of patients with DLCL with marrow infiltration, appears not to influence the PFS & OS. However, an increasing degree of marrow involvement is associated with an increasing component of large cells and a poorer prognosis in DLCL patients, independent of other risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 23 publications
4
74
2
4
Order By: Relevance
“…18 F]-FDG PET was not predictive of BM pathology [12,13,16,[19][20][21][22][23][24]. This is also our point of view and we believe that it should be ���������������������������������� MIP and axial images from a 35 year old male shows focal FDG uptake at the lower thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…18 F]-FDG PET was not predictive of BM pathology [12,13,16,[19][20][21][22][23][24]. This is also our point of view and we believe that it should be ���������������������������������� MIP and axial images from a 35 year old male shows focal FDG uptake at the lower thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…This is a higher degree of concordant involvement than has been reported by Chung et al (2007) (?50%) and Campbell et al (2006) (?28%) and may be caused by involvement being measured on IHC rather than routine histology. Although a trend toward better survival was noted with discordant rather than concordant involvement, this was not statistically significant and may be because of the small numbers, especially when cases treated with palliative intent were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Marrow involvement in DLBCL has implications for prognosis; lymphomatous infiltration in the marrow has been reported to correlate with poor survival (Yan et al 1995;Campbell et al 2006). Furthermore, marrow involvement in DLBCL affects the International Prognostic Index (IPI) both by increasing the stage of the disease to stage IV and by being assessed as extranodal involve ment (Shipp et al 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the infiltration of lymphoma is usually focal, biopsy can miss the infiltration and the size of the biopsy may be too small to evaluate the infiltration. Although, some studies support the need for bilateral biopsies [4], others concluded that a specimen long enough (approximately 2 cm) may obviate the need for bilateral sampling [5].…”
Section: Introductionmentioning
confidence: 99%